Infertile human endometrial organoid apical protein secretions are dysregulated and impair trophoblast progenitor cell adhesion - Zhou, Wei; Barton, Siena; Cui, Jinwei; Santos, Leilani L.; Yang, Guannan; Stern, Catharyn; Kieu, Violet; Teh, Wan Tinn; Ang, Catarina; Lucky, Tarana; Sgroi, Joseph; Ye, Louie; et al. (Frontiers in Endocrinology, 2022)
Embryo implantation failure leads to infertility. As an important approach to regulate implantation, endometrial epithelial cells produce and secrete factors apically into the uterine cavity in the receptive phase to prepare the initial blastocyst adhesion and implantation. We established organoids using endometrial biopsies from women with normal fertility and primary infertility and treated them with hormones to model the receptive phase endometrial epithelium. Our data show that infertile organoids were dysregulated in their response to estrogen and progesterone treatment. Proteomic analysis of organoid apical secretions identified 150 dysregulated proteins between fertile and infertile groups (>1.5-fold change). Trophoblast progenitor spheroids (blastocyst surrogates) treated with infertile organoid apical secretions significantly compromised their adhesion to organoid epithelial cell monolayers compared to fertile group (P < 0.0001). Overall, this study paves the way to determine the molecular mechanisms by which endometrial epithelial apical released factors regulate blastocyst initial attachment and implantation.